From Empowerment to Control? The Case of a National Programme for Young People in Peripheral Territories - Abrantes, P.; Raposo, Otávio; Ferro, L.; Varela, Pedro; Lacerda, Beatriz; Moreira, Liliana; Seabra, T.; Lopes, J.M.T. (16th European Sociological Association Conference (ESA 2024), 2024)
This paper aims to discuss public policies for young people in peripheral areas, exploring the case of the main programme in Portugal on this area, launched in 2001 and currently supporting 118 local projects throughout the country. Based on the international literature on social policies for vulnerable youth integration, sketching different models and ongoing controversies, we will provide a systematic analysis of the institutional guides of the 9 editions of the program insofar (from 2001 to 2023), as well as external evaluation reports and other studies. Besides, we will enrich our analysis with data collected from interviews with national board members and project local coordinators, as well as some statistical data regarding territories, target-groups and methodological approaches privileged in different editions. Our main goal is to sketch the main trends and challenges in Escolhas programme, as a way to contribute to the international knowledge on social policies for young people in poor outcasts. Although the programme’s rationale tends to focus on young people as individuals, our analysis takes into account their structural position, as members of segregated communities. A key issue is how such interventions are actually integrating, empowering and/or controlling young people, as well as which groups are involved and which ones tend to be aside. The ability to effectively improve young people’s conditions – on wellbeing, safety, employment, education, political participation, social capital – is examined, along with the impact on the whole communities, while the risk of generating new illusive promises, dependencies and exclusions is discussed.